Lipoedema – myths and facts, Part 5 - Bertsch, Tobias; Erbacher, Gabriele; Corda, D.; Damstra, R. J.; van Duinen, K.; Elwell, R.; van Esch-Smeenge, J.; Faerber, G.; Fetzer, S.; Fink, J.; Fleming, A.; Frambach, Y.; Gordon, K.; Hardy, D.; Hendrickx, A.; Hirsch, T.; Koet, B.; Mallinger, P.; Miller, A.; Moffatt, C.; Torio-Padron, N.; Ure, C.; Wagner, S.; Zähringer, T. (Phlebologie, 2020)
The four previous articles in this series addressed the myths and facts surrounding lipoedema. We have shown that there is no scientific evidence at all for the key statements made about lipoedema – which are published time and time again. The main result of this “misunderstanding” of lipoedema is a therapeutic concept that misses the mark. The patient’s real problems are overlooked.The national and especially the international response to the series, which can be read in both German and English, has been immense and has exceeded all our expectations. The numerous reactions to our articles make it clear that in other countries, too, the fallacies regarding lipoedema have led to an increasing discrepancy between the experience of healthcare workers and the perspective of patients and self-help groups, based on misinformation mostly generated by the medical profession.Parts 1 to 4 in this series of articles on the myths surrounding lipoedema have made it clear that we have to radically change the view of lipoedema that has been held for decades. Changing our perspective means getting away from the idea of “oedema in lipoedema” – and hence away from the dogma that decongestion is absolutely necessary – and towards the actual problems faced by our patients with lipoedema. Such a paradigm shift in a disease that has been described in the same way for decades cannot be left to individuals but must be put on a much broader footing. For this reason, the lead author of this series of articles invited renowned lipoedema experts from various European countries to discussions on the subject. Experts from seven different countries took part in the two European Lipoedema Forums, with the goal of establishing a consensus. The consensus reflects the experts’ shared view on the disease, having scrutinized the available literature, and having taken into account the many years of clinical practice with this particular patient group. Appropriate to the clinical complexity of lipoedema, participants from different specialties provided an interdisciplinary approach. Nearly all of the participants in the European Lipoedema Forum had already published work on lipoedema, had been involved in drawing up their national lipoedema guidelines, or were on the executive board of their respective specialty society.In this fifth and final part of our series on lipoedema, we will summarise the relevant findings of this consensus, emphasising the treatment of lipoedema as we now recommend it. As the next step, the actual consensus paper “European Best Practice of Lipoedema” will be issued as an international publication.Instead of looking at the treatment of oedema, the consensus paper will focus on treatment of the soft tissue pain, as well as the psychological vulnerability of patients with lipoedema. The relationship between pain perception and the patient’s mental health is recognised and dealt with specifically. The consensus also addresses the problem of self-acceptance, and this plays a prominent role in the new therapeutic concept. The treatment of obesity provides a further pillar of treatment. Obesity is recognised as being the most common comorbid condition by far and an important trigger of lipoedema. Bariatric surgery should therefore also be considered for patients with lipoedema who are morbidly obese. The expert group upgraded the importance of compression therapy and appropriate physical activity, as the demonstrated anti-inflammatory effects directly improve the patients’ symptoms. Patients will be provided with tools for personalised self-management in order to sustain sucessful treatment. Should conservative therapy fail to improve the symptoms, liposuction may be considered in strictly defined circumstances.The change in the view of lipoedema that we describe here brings the patients’ actual symptoms to the forefront. This approach allows us to focus on more comprehensive treatment that is not only more effective but also more sustainable than focusing on the removal of non-existent oedema.Die Mythen und Fakten des Lipödems waren das Thema der vergangenen 4 Teile dieser Artikelserie. Wir konnten zeigen, dass für die zentralen – und immer wieder publizierten – Statements zum Lipödem keinerlei wissenschaftliche Evidenz vorliegt. Wesentliche Folge dieses „Fehlverständnisses“ der Erkrankung Lipödem ist ein Therapiekonzept, welches an den tatsächlichen Beschwerden der Patientinnen weitgehend vorbeigeht.Der nationale, aber vor allem auch der internationale Zuspruch, der auch in Englisch zu lesenden Reihe, war immens und übertraf all unsere Erwartungen. Die zahlreichen Reaktionen auf unsere Artikelserie machten eines deutlich: Auch in anderen Ländern führen die Stilblüten des Lipödems zu einer zunehmenden Diskrepanz zwischen den Erfahrungen der Behandler und der durch – meist ärztlich verursachten – Fehlinformation geleiteten Perspektive der Patientinnen und Selbsthilfegruppen.Die Teile 1 bis 4 der Artikelserie über die Mythen des Lipödems haben deutlich gemacht, dass wir diese seit Jahrzehnten tradierte Perspektive auf die Erkrankung Lipödem verändern müssen. Veränderung der Perspektive heißt: Weg vom „Ödem im Lipödem“, damit auch weg vom Dogma der notwendigen „Entstauung“ und hin zu den tatsächlichen Beschwerden unserer Lipödem-Patientinnen. Ein solcher Paradigmenwechsel eines seit Jahrzehnten auf immer gleiche Weise beschriebenen Krankheitsbildes kann nicht Aufgabe Einzelner sein, sondern muss auf breite Füße gestellt werden. Aus diesem Grund hat der ärztliche Erstautor dieser Artikelreihe renommierte Lipödem-Experten aus verschiedenen europäischen Ländern zu einer Diskussion über das Lipödem eingeladen. Ziel der beiden „European Lipoedema-Foren“, an denen Experten aus 7 Ländern teilnahmen, war die Erstellung eines Konsensus. Dieser Konsensus spiegelt unter Sichtung der zur Verfügung stehenden wissenschaftlichen Literatur – bei gleichzeitiger Berücksichtigung der jeweils langjährigen klinischen Arbeit mit diesen Patientinnen – die gemeinsame Sicht der beteiligten europäischen Experten auf diese Erkrankung wider. Der Komplexität des Krankheitsbildes Lipödem angemessen war auch die Struktur der Teilnehmer interdisziplinär. Nahezu alle Teilnehmer des European Lipoedema-Forum haben in der Vergangenheit entweder über das Lipödem publiziert bzw. an ihren nationalen Lipödem-Leitlinien mitgearbeitet oder sind in Vorständen ihrer Fachgesellschaften vertreten.In diesem fünften und letzten Teil unserer Artikelserie über das Lipödem sollen vorab die wesentlichen Ergebnisse dieses Konsensus kurz zusammengefasst werden, wobei der Fokus auf der empfohlenen Therapie des Lipödems liegt. Das eigentliche Konsensus-Papier, „European Best Practice of Lipoedema“, wird dann in einem zweiten Schritt im Rahmen einer internationalen Publikation veröffentlicht.Statt einer Ödem-Behandlung wird im Konsensus-Papier auf die Behandlung des Weichteilschmerzes ebenso fokussiert wie auf die psychische Vulnerabilität der Lipödem-Patientin. Zusammenhänge zwischen der Schmerzwahrnehmung und der psychischen Situation der Patientin werden anerkannt und gezielt behandelt. Hierbei wird auch das Problem der Selbstakzeptanz thematisiert und spielt im neuen Behandlungskonzept eine herausragende Rolle. Eine weitere Therapiesäule stellt die Adipositas-Behandlung dar. Adipositas wird somit als mit Abstand häufigste Begleiterkrankung – und wesentlicher Trigger – des Lipödems akzeptiert. Bei schwer adipösen Lipödem-Patientinnen sollte daher auch die bariatrische Operation erwogen werden. Kompressionstherapie und gezielte Bewegungsaktivität wurden von der Expertengruppe deutlich aufgewertet, da durch die nachgewiesenen antiinflammatorischen Effekte die Beschwerden der Patienten direkt verbessert werden. Durch ein individualisiertes Selbstmanagement werden den Patientinnen Tools mit an die Hand gegeben, die den Therapieerfolg nachhaltig stabilisieren. Sollte die konservative Therapie zu keiner relevanten Beschwerdebesserung führen, kann die Liposuktion unter Einhaltung klar definierter Vorgaben erwogen werden.Die hier beschriebene Veränderung der Perspektive auf das Lipödem stellt die tatsächlichen Beschwerden der Patientinnen in den Fokus. Dies ermöglicht eine umfassendere, damit bessere und auch nachhaltigere Behandlung als die Fokussierung auf ein nie nachgewiesenes Ödem und dessen Entstauung.
Keywords: lipoedema; paradigm shift; european consensus; therapy